Landscape and within-field factors affecting the damages of the brassica pod midge (Dasineura brassicae) in Swedish winter oilseed rape cultivation - Rösvik, Axel (2019)
The brassica pod midge (Dasineura brassicae) has been a serious upcoming problem in Swedish oilseed cultivation during recent years. This small dipteran utilized pods damaged by its facilitator, the cabbage seed weevil (Ceutorynchus obstrictus), to be able to oviposit. The larvae of D. brassicae feed on the inner pod wall, causing the pod to split prematurely and releasing its seeds, which causes yield loss for the farmer. In this study, we investigate how landscape and within-field factors such as previous years percentage of oilseed rape in the landscape, landscape complexity, distance to previous years oilseed rape field, abundance of C. obstrictus and chemical treatments affect the damages caused by D. brasssicae. This was done on 19 locations in Skåne, the southernmost province of Sweden. Yellow pan traps and yellow sticky traps were used to monitor the C. obstrictus populations. Information on chemical treatments were gathered by contacting the farmers. The landscape parameters where assessed using geographical information systems and data from the Swedish Board of Agriculture and the Swedish Environmental Protection Agency. Our results showed a positive correlation between abundance of C. obstrictus and damages caused by D. brassicae. Both abundance of C. obstrictus and damage from D. brassicae showed a positive correlation with an increasing landscape complexity at a small distance (1000m), C. obstritcus also showed a positive correlation at larger distances (2000-4000m). However, no correlation was found between an increasing percentage of previously cultivated winter oilseed rape and the damages from D. brassicae or abundance of C. obstrictus. Some regions within the province showed a significantly higher amount of damage than others; these provinces generally contained a more complex landscape compared to the ones where surveys had shown less damage. Stepwise multiple regression models with the within-field and landscape factors as independent variables showed that previous year’s percentage of oilseed rape had a positive impact on the damages caused by D. brassicae during the entire season. In the late pod set, the abundance of C. obstrictus also had a positive impact on the damages caused by D. brassicae. However, the chemical treatment did not seem to affect the damages caused by D. brassicae in late pod set in any way.